How foundations work what grantseekers need to know about the many faces of foundations - McIlnay, Dennis P. 1948- (Jossey-Bass Publishers, 1998)
In this groundbreaking book, Dennis McIlnay offers a unique and remarkable look inside foundations--exploring the complex workings of the mysterious and often misunderstood organizations that so often determine the success or failure of a nonprofit's fund raising ventures. Drawing on his extensive research and on insights from foundations, McIlnay gives the grantseeker an edge in the highly competitive world of foundation grants by both debunking many of the myths and misconseptions surrounding foundations and including more productive strategies for dealing with them. Structured around six perceptions of foundations--judges, editors, citizens, activists, entrepreneurs, and partners--this book provides a thorough understanding of what makes foundations tick and how this affects their interations with nonprofits.
Includes bibliographical references (pages 175-192) and indexes. - Print version record
Keywords: Endowments -- United States; Research grants -- United States; Fund raising -- United States; Fondations; États-Unis; Bourses de recherche; États-Unis; Collecte de fonds; États-Unis; Endowments; Fund raising; Research grants; Stichtingen; Subsidies; Fondsenverwerving; Social Welfare & Social Work; Social Sciences; Social Welfare & Social Work - General; United States